Solvent‐Controlled Copper‐Catalyzed Oxidation of Benzylic Alcohols to Aldehydes and Esters. Issue 21 (12th June 2013) - Zhu, Yefeng; Wei, Yunyang
Abstract: A procedure for the copper‐catalyzed selective oxidation of primary alcohols to esters and aldehydes was developed. Under solvent‐free conditions, self‐oxidative esterification and cross‐esterification of benzyl alcohols with various aliphatic alcohols proceed smoothly to give the corresponding esters in good yields. If DMF was used as a solvent, the benzyl alcohols were selectively converted into the corresponding aldehydes in excellent yields. Abstract : Depend on solvent! Under solvent‐free conditions, Cu‐catalyzed oxidative self‐esterification and cross‐esterification of benzylic alcohols with various aliphatic alcohols proceed smoothly to give the corresponding esters in good yields. If DMF is used as a solvent, the benzylic alcohols are selectively converted into the corresponding aldehydes in excellent yields. DTBP = di‐ tert ‐butyl peroxide.